Understanding the post-curing behaviors of polymethylacrylimide: Curing kinetics and molecular mobility - Yuan Chen; Xiaolian Qiang; Yaping Zhang; Ningning Song; Lixian Guo; Siyuan Zhang; Chunrong Tian; Keping Chen (Polymer Testing)
In this study, the post-curing kinetic, molecular mobility and mechanical behavior of polymethylacrylimide (PMI), synthesized from methacrylic acid and methacrylonitrile, were systematically investigated. Differential scanning calorimetry results identified three distinct temperature zones during the post-curing process, which represented different types of curing reactions. Model-free kinetic methods were used to evaluate the post-curing kinetics of PMI materials. Fourier transform infrared spectroscopy demonstrated that the cyclization of anhydride groups predominantly occurred at lower post-curing temperatures, while the decomposition and transformation were observed at higher temperatures. Meanwhile, there was a progressive formation of imide rings with the increase of post-curing temperature. In addition, the molecular segment mobility of PMI materials was investigated via dielectric relaxation spectroscopy, and molecular segment mobility was gradually restricted during the post-curing process, indicated the formation of crosslinked network structure. Those changes of microstructures agreed well with the evolution of compressive properties. This study provides insights into the curing kinetics and structural evolution of PMI during post-curing process, offering guidance for optimizing post-curing conditions to achieve superior mechanical performance.